Factors Affecting Consumer Satisfaction of E-Sewa and Khalti in Nepal (SADGAMAYA, 2026)
The study analyzes the Factors affecting consumer satisfaction with E-Sewa and Khalti in Nepal. The dependent Variable for the study was customer satisfaction, while the independent variables were service quality, mode of delivery, Risk, price charged, and knowledge. The study was based on primary data. Primary data were collected through the online questionnaires. The descriptive and causal comparative research designs were used. The sample for this study was 384. The respondents were selected using simple random sampling. The study found that increasing knowledge of these digital payment platforms can also lead to increased customer satisfaction. The Risk of using these digital payment platforms also positively impacts customer satisfaction, and companies should be aware of the Risk and customers' perception of Risk when developing and marketing their services.